Cache-Aware Task Partitioning for Multicore Real-Time Systems - Starke, Renan Augusto; Oliveira, Romulo Silva de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
The correct functioning of real-time systems depends not only on the logically correct response, but also the time when it is given. This type of application is increasingly present today and the processing demand is such that complex multi-core processors are needed. The development of multiprocessor is ahead of the techniques of analysis of such systems and it is therefore necessary further research to promote reliability and to reduce over-specified systems. In modern processors, task preemption introduces indirect cost related to the cache memory. A preemption evicts a large amount of memory blocks from the cache memory during the preempting time interval. In this paper we present a partitioning heuristic that includes the cache related preemption delay assumptions in a multiprocessor system with cache memory focusing in partitioned fixed priority preemptive scheduling.